1995
DOI: 10.1038/nsb0995-777
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-induced structural changes and domain autonomy in calmodulin

Abstract: We have determined the solution structures of the apo and (Ca2+)2 forms of the carboxy-terminal domain of calmodulin using multidimensional heteronuclear nuclear magnetic resonance spectroscopy. The results show that both forms adopt well-defined structures with essentially equal secondary structure. A comparison of the structures of the two forms shows that Ca2+ binding causes major rearrangements of the secondary structure elements with changes in inter-residue distances of up to 15 A and exposure of the hyd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
265
2

Year Published

1997
1997
2007
2007

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 302 publications
(292 citation statements)
references
References 37 publications
25
265
2
Order By: Relevance
“…Complementary insights were also obtained from a corresponding analysis of TnC, made by comparing the apo N-terminal domain from the X-ray crystal structure (Satyshur et al, 1994) and the N-terminal domain from the Ca2+-loaded NMR structure (Slupsky & Sykes, 1995). In all cases, the comparisons of the closed and open conformations confirm that Ca2+ binding causes opening within each of the EF-hands, as first predicted by the HMJ model based on the crystal structure of TnC (Herzberg et al, 1986), and subsequently confirmed by NMR solution structures of CaM and TnC (Finn et al, 1995;GagnC et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995).…”
Section: Caz'-induced Transition From the Closed To Open Conformationmentioning
confidence: 64%
See 1 more Smart Citation
“…Complementary insights were also obtained from a corresponding analysis of TnC, made by comparing the apo N-terminal domain from the X-ray crystal structure (Satyshur et al, 1994) and the N-terminal domain from the Ca2+-loaded NMR structure (Slupsky & Sykes, 1995). In all cases, the comparisons of the closed and open conformations confirm that Ca2+ binding causes opening within each of the EF-hands, as first predicted by the HMJ model based on the crystal structure of TnC (Herzberg et al, 1986), and subsequently confirmed by NMR solution structures of CaM and TnC (Finn et al, 1995;GagnC et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995).…”
Section: Caz'-induced Transition From the Closed To Open Conformationmentioning
confidence: 64%
“…a representative non-sensor protein, has been reported previously (Akke et al, 1995;Skelton et al, 1995). The general features of Ca'+-induced conformational changes in CaM and TnC were described when the structures of their apo state were first reported (Finn et al, 1995;Gagnt et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995). However, these descriptions did not reveal the underlying structural basis for the response to Ca2+ binding.…”
mentioning
confidence: 99%
“…This approach is justified by observations that the Ca2+ binding profile of free CaM can be reconstructed from those of its two isolated domains, by evidence for domain-independence in the binding and dissociation of Ca2+ in CaM-target complexes, and by the observation that individual Ca2+ site mutations perturb mainly the two sites in the same domain (Linse et al, 1991;Starovasnik et al, 1992;Finn et al, 1995;Bayley et al, 1996;Johnson et al, 1996). Table 2 presents the resulting equilibrium dissociation constants and Hill coefficients of the high-affinity ( K D l , H I ) and low affinity (KD2, Hz) CaM domains.…”
Section: Measurements Of Ca2+ Binding To Cam-peptide Complexesmentioning
confidence: 99%
“…CaM has a dumbbell shaped structure in which two domains, termed the N and C domains, are linked by a flexible helix (Taylor et al, 1991;Finn et al, 1995;Kuboniwa et al, 1995;Zhang et al, 1995). Each domain binds two Ca2+ ions into a pair of EF-hand type sites.…”
mentioning
confidence: 99%
“…Comparison of the N-terminal region of Helix B of N-CaM (A) and Ca 2+ -loaded CaM (1CLL). The segments of the helix that are in a traditional alpha-helical configuration are colored rose red, while the most N-terminal portion of the helix in our structure displays a 3 10 -helical conformation and is colored magenta. The oxygen and nitrogen of residues are colored red and blue, respectively.…”
Section: Supplementary Materialsmentioning
confidence: 99%